GIANT-CELL RICH ATRIAL MYXOMA: REPORT OF TWO CASES AND REVIEW OF LITERATURE - Tariq, Hina; Mamoon, Nadira (Journal of Ayub Medical College Abbottabad, 2016)
The cases of two middle age males are presented who were incidentally diagnosed to have atrial myxoma. Both of them underwent successful surgical interventions. Histologically, both myxomas showed abundant multinucleated giant cells, in addition to typical myxoid stroma with stellate and cord-like structures.